Além de Bem e Mal: a fisiopsicologia enquanto investigação da metafísica - Mello, Marioni Fischer de (2013)
Peering into the last period of Nietzschean writings, it is clear that the philosopher, through his critique of metaphysics, deepens the antagonism against his time. In this context, the objective of this study is to show that Nietzschean phisiopsychology constitutes an investigative procedure that establishes the conditions for the emergence of a "philosophy of the future", i.e. that what, for purposes of this study, is called a true "philosophy of effectiveness" (Wirklichkeit). This task requires the overcoming of metaphysics, enabling the emergence of new philosophers committed to life. Therefore, in the first chapter, we sought to investigate the multiple senses in which Nietzsche uses the term psychology and the proper meaning of Nietzschean phisiopsychology, and took into consideration the Nietzscheanmeaning of physiology: a dynamic of struggle of impulses for more power. Beyond the duality body/soul, Nietzsche proposes a phisiopsychology as morphology and developmental theory of the will to power. In the second chapter, the intention is to clarify what the philosopher meant by metaphysics and show that its phisiopsychology is the antagonistic procedure to that used by the dogmatics pursuing absolute truths. In the third chapter, we proceed to phisiopsychological research on metaphysics, seeking to understand what is their role in the emergence of the "philosophy of effectiveness" (Wirklichkeit). To elucidate these aspects, the research focused on the work Beyond Good and Evil (Jenseits von Gut und Böse, 1885/86). This procedure is justified because it is in this text that Nietzsche explicitly refers to his notion of phisiopsychology, though, as investigation of symptoms, it has been steadily used by the philosopher. Moreover, it is in Beyond Good and Evil that Nietzsche, having performed his positive task in Thus Spoke Zarathustra, contemplates his negative task of destroying prevailing values, aiming at the emergence of the philosophers of the future. The subtitle of the book, it should be remembered, is Prelude to a philosophy of the future. The task which is imposed on Nietzsche is to create new values, breaking the Platonic-Christian moral that founded the metaphysics and pointing to the "philosophy of effectiveness" (Wirklichkeit). This philosophy of the future devotes life as a criterion, states coming-to-be and change, rejecting fixed and transcendent notions. To Nietzsche, a separation between psychology and physiology are also dependent of the metaphysical duality of absolute qualitative opposites. The Nietzschean phisiopsychology is a first step toward the "philosophy of effectiveness"(Wirklichkeit).